DETERMINANTS OF TECHNICAL EFFICIENCY IN IRRIGATED TOMATO PRODUCTION UNDER KANO RIVER IRRIGATION PROJECT, PHASE I - Ahmed, Bashir Sa'ad (FUDMA JOURNAL OF SCIENCES, 2023)
The present study has estimated the Determinants of Technical Efficiency in Irrigated Tomato Production under Kano River Irrigation Project, Phase I. Primary data were collected from 213 irrigated tomato farmers, using multi-stage sampling techniques in three local government areas covered by KRIP. Data were collected during the 2014/2015 irrigation farming season using structured questionnaire. Data collected were analyzed using two-stage Data Envelopment Analysis (DEA) and regression models.   Findings further revealed that none of the sampled irrigated tomato farmer reached the frontier threshold. Also, factors such as age, household size, farming experience, sources of finance, sex and cooperative society were responsible for 59% total variation in technical efficiency among the three categories of irrigated tomato farms. Based on the findings of this study, it can be concluded that age, household size, farming experience, amount of credit, extension contact, cooperative societies and sex were the determinants of technical efficiency were for all the three categories of farms. It was therefore, recommended that since cooperative membership was a significantly determinant of technical efficiency, irrigated tomato farmers should join cooperative societies, so as to be able to benefit from the government and non-governmental organisations through increased credit access, input supply and farm advisory services
Keywords: Tomato, Production, Irrigation, Technical Efficiency, Kano-River